THE INFLUENCE OF EDUCATION USING MODIFICATION MODULE ON KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF PREGNANCY CARE IN KENDARI, INDONESIA - Kartini, Kartini; Syafar, Muh; Arsin, Arsunan A.; Bahar, Burhanuddin; Fitriyanti, Fitriyanti; Farming, Farming (Public Health of Indonesia, 2016)
Background: Prenatal care is one way to prevent complications of pregnancy, and educational approach is the best approach to improve the knowledge of mothers about prenatal care.Aim: This study aimed to determine the influence of education on knowledge, attitude, and behavior of pregnancy care in Kendari, IndonesiaMethods: This was Quasi Experimental study with pre-post design. There were 4 groups involved in this study, which were: 1) The group that received educational intervention using a modification module from the MHC book of the Department of Health, 2) The group that received educational intervention using MHC book of the Department of Health, 3) The group that only used modification modules from MHC book of the Department of Health, and 4) The group that only used the MHC book of Department of Health. The intervention was given for 6 months. Seventy eight of 4-months pregnant women were selected by purposive sampling. Data were collected by asking the respondents to fulfill the questionnaires, which adopted from the questionnaire of Faculty of Public Health, Hasanuddin University to measure knowledge (15 items), attitude (18 items), and behaviors (15 items) of respondents. Data were analyzed by using Wilcoxon test and Kruskal Wallis test.Results: Results showed thre was an influence of education on knowledge, attitude, and behavior of pregnancy care. Improvement in knowledge, attitudes, and behavior of pregnancy care was higher in the group  of pregnant women using a modification moduleConclusion: Education through the class of pregnant woman has an impact to increase knowledge, attitude, and behavior of care of pregnant woman. It is therefore the efforts to maintain educational approach is necessary.